Synchronization through nonreciprocal connections in a hybrid hippocampus microcircuit - Hilscher, Markus M.; Leão, Katarina E.; Leão, Richardson N. (Frontiers in Neural Circuits, 2013)
Synchronisation among neurons is thought to arise from the interplay between excitation and inhibition; however, the connectivity rules that contribute to synchronisation are still unknown. We studied these issues in hippocampal CA1 microcircuits using paired patch clamp recordings and real time computing. By virtually connecting a model interneuron with two pyramidal cells (PCs), we were able to test the importance of connectivity in synchronising pyramidal cell activity. Our results show that a circuit with a nonreciprocal connection between pyramidal cells and no feedback from PCs to the virtual interneuron produced the greatest level of synchronisation and mutual information between PC spiking activity. Moreover, we investigated the role of intrinsic membrane properties contributing to synchronisation where the application of a specific ion channel blocker, ZD7288 dramatically impaired PC synchronisation. Additionally, background synaptic activity, in particular arising from NMDA receptors, has a large impact on the synchrony observed in the aforementioned circuit. Our results gives new insights to the basic connection paradigms of microcircuits that lead to coordination and the formation of assemblies.